Innovative features of the modern role of artificial intelligence in surgery - Bilodid , Vladyslav; Welgan , Katarzyna (The Ukrainian Scientific Medical Youth Journal, 2024)
the article is dedicated to exploring innovative aspects of contemporary trends in the application of artificial intelligence in surgery. The paper provides an analysis of the scientific discourse regarding the impact of artificial intelligence on the development of surgical techniques and the improvement of diagnostic accuracy and surgical intervention effectiveness. The aim of the article is to examine and analyze the innovative features of artificial intelligence in modern surgery. To assess the current state of research on the use of Artificial Intelligence in surgery, a systematic search of scientific publications in various databases was conducted. The information from selected publications was then systematized and integrated to identify key trends in the use of AI in surgery and to synthesize the results for determining innovative aspects and challenges. The article includes an analysis comparing contemporary software products of robotic surgical systems based on artificial intelligence algorithms. The achieved results in this review and analysis of innovative features of artificial intelligence in surgery indicate a significant contribution of this technology to modern medical practice, where the use of artificial intelligence in surgery contributes to a substantial improvement in diagnostic accuracy and surgical planning, thereby affecting the overall efficiency of medical interventions.